Variability and evolution of Kaposi's sarcoma-associated herpesvirus in Europe and Africa. International Collaborative Group. - Cook PM; Whitby D; Calabro ML; Kakoola DN; Hjalgrim H; Ariyoshi K; Ensoli B; Davison AJ; Schulz T.F.; LUPPI, Mario (1999)
OBJECTIVE: To study the evolution of Kaposi's sarcoma-associated herpesvirus (KSHV) or human herpesvirus type 8 in Europe and Africa.DESIGN AND METHODS: PCR and sequence analysis of the variable viral membrane glycoprotein gene K1 in 58 tumour and peripheral blood samples from patients with AIDS-related Kaposi's sarcoma (KS), 'classic' (HIV-negative) KS, transplant KS, Multicentric Castleman's Disease, other lymphoproliferative disorders, and healthy KSHV-infected individuals from the UK, Denmark, Sweden, Italy, Spain, Iceland, The Faroe Islands, Greece, The Gambia and Uganda.RESULTS: Three major groups of K1 sequences were found: A, B and C, as defined previously. The K1 gene has evolved, both within and between these three groups, under positive selection. KSHV group B strains predominate in Africa and are more distant from groups A and C, found in Europe, than A and C are from each other. Within group C two subgroups, C' and C", can be identified. Subgroup C" is more closely related to group A in a region of the K1 protein and appears to be phylogenetically close to the branchpoint between A and C. Group A and C strains are currently found in both HIV-1-infected and -uninfected Europeans, and were already present in Europe before the start of the AIDS epidemic. We found some examples of closely related K1 sequences in Italy and Denmark, but in general KSHV strains in Europe did not cluster geographically.CONCLUSION: KSHV strains in East and West Africa are closely related but phylogenetically distant from those in Europe. The two major KSHV groups in Europe are more closely related, with some strains adopting an intermediate phylogenetic position. In Europe, KSHV strains may have been disseminated at least several decades ago. Variability in the K1 region is driven by selection and does not correlate with different KSHV-related pathologies or geographic regions where clinically more aggressive HIV-negative KS ('endemic' KS) is more common.